Fabrication of single Ga-doped ZnS nanowires as high-gain photosensors by focused ion beam deposition. (4th September 2017) - Yen, Shih-Hsiang; Hung, Yu-Chen; Yeh, Ping-Hung; Su, Ya-Wen; Wang, Chiu-Yen
Abstract: ZnS nanowires were synthesized via a vapor–liquid–solid mechanism and then fabricated into a single-nanowire field-effect transistor by focused ion beam (FIB) deposition. The field-effect electrical properties of the FIB-fabricated ZnS nanowire device, namely conductivity, mobility and hole concentration, were 9.13 Ω −1 cm −1, 13.14 cm 2 V −1 s −1 and 4.27 × 10 18 cm −3, respectively. The photoresponse properties of the ZnS nanowires were studied and the current responsivity, current gain, response time and recovery time were 4.97 × 10 6 A W −1, 2.43 × 10 7, 9 s and 24 s, respectively. Temperature-dependent I – V measurements were used to analyze the interfacial barrier height between ZnS and the FIB-deposited Pt electrode. The results show that the interfacial barrier height is as low as 40 meV. The energy-dispersive spectrometer elemental line scan shows the influence of Ga ions on the ZnS nanowire surface on the FIB-deposited Pt contact electrodes. The results of temperature-dependent I – V measurements and the elemental line scan indicate that Ga ions were doped into the ZnS nanowire, reducing the barrier height between the FIB-deposited Pt electrodes and the single ZnS nanowire. The small barrier height results in the FIB-fabricated ZnS nanowire device acting as a high-gain photosensor.